BUDIDAYA TANAMAN MELATI DI WILAYAH PESISIRDENGANBAHAN ORGANIK: SARANA PEMBELAJARANEKOLOGI - Ari Handriatni (LPMPP Universitas Negeri Yogyakarta, 2008)
Many fertile land areas in Indonesia are used for office buildings and newresidential areas. Therefore, agricultural .land areas decrease. The agriculturalproductivity increment through extensive land useshould be directed to marginalland such as beaches. Beaches will be suitable for jasmine cultivationwith organicfertilizer treatment. This action can also serve asan ecological practice. Academicsociety, including students,and people in general can do it·together in beaches